The Effects of Harvesting Period and Inoculant on Second-Crop Maize Silage Fermentative Quality - LORENZO SERVA; GIORGIO MARCHESINI; LUISA MAGRIN; Arzu Peker; SEVERINO SEGATO (Agronomy, 2024)
Southern Europe’s mutating weather conditions and the European environmental agenda have suggested the cropping of maize (Zea mays L.) after winter cereal cultivation, even if shortening the growing period could result in an immature harvesting stage, limiting its silage quality. The experimental design investigated the effects of four harvesting dry matter (DM) classes (DMvl, 23.9%; DMl, 25.3%; DMm, 26.2%; DMh, 30.4%) in two inoculant types (heterofermentative (HE) vs. homofermentative (HOM) on fermentative quality, DM losses, and aerobic stability. The early harvested DMvl and DMl classes had the lowest silage density (<130 kg m−3) and resulted in an organic acids profile lowering the fermentative quality and increasing the DM losses, while no differences were detected following the use of the inoculants. The aerobic stability was more susceptible to further adverse fermentation via opportunistic microorganisms in the DMm and DMh classes, probably due to the lower moisture content, but the use of both HE and HOM lactic acid bacteria seemed to contain this silage surface damage. In summary, a shortening of the maize growing period might limit the achievement of the maturity stage ideal for high-quality silage, hampering the positive effects of both HOM and HE inoculants in the ensiling process of early harvested maize.